Combined treatment of drug-resistant tuberculosis with bedaquiline and delamanid: a systematic review. Issue 1 (5th July 2018) - Pontali, Emanuele; Sotgiu, Giovanni; Tiberi, Simon; Tadolini, Marina; Visca, Dina; D'Ambrosio, Lia; Centis, Rosella; Spanevello, Antonio; Migliori, Giovanni Battista
The World Health Organization (WHO) estimated that 490 000 cases of multidrug-resistant (MDR) tuberculosis (TB) (defined as TB caused by Mycobacterium tuberculosis strains resistant to at least isoniazid and rifampicin) occurred in 2016. Among them, ∼6.2% had extensively drug-resistant (XDR) TB ( i.e. TB caused by MDR strains with additional resistance to fluoroquinolones and at least one second-line injectable drug) [1]. Efficacy and safety of co-administered bedaquiline and delamanid in MDR-TB patients http://ow.ly/Ctvj30kreEP